Joint Efficiency And Average Burn-Off Length Of Friction Welded ABS Ter-Polymers - Jwan Khaleel Mohammed (Eurasian Journal of Science and Engineering, 2023)
Welding is one of the most efficient techniques used throughout the decades. Among different techniques, friction welding being one of the most sufficient methods. In addition, polymer is one of the materials that has wide applications such as automobiles, aerospace, medical etc. The present study has been carried out to investigate the efficiency of similar friction-welded ABS terpolymer joints. The study was conducted using the rotary friction welding method. Three different cases of rotational friction speeds (605, 820, 1220 rpm) and times (15, 30, 60 seconds) were examined for each case by taking nine specimens. The tensile strength of welded joints is compared to that of ABS tensile specimen as received welding. The joint efficiency and burn-off length were calculated. The joint efficiency and burn-off results are compared and discussed. Then the study concluded that the optimum joint efficiency was 17.24% at 605 rpm and 60 seconds. The lower burn-off length was 2 mm at 605 rpm and 15 seconds.